Vaksinasi Influenza sebagai Prediktor Terjadinya Kejadian Rawat Inap Akibat Kejadian Kardiovaskular pada Pasien dengan Riwayat Penyakit Jantung Koroner: Suatu Laporan Kasus Berbasis Bukti - Koesnoe, Sukamto; Johan, Alvin; Dewanta, Widhi; Ekanara, Nabilla Gita; Hermanadi, Muhammad Ikrar (Jurnal Penyakit Dalam Indonesia, 2023)
Influenza is known to worsen cardiovascular events in patients with a history of coronary heart disease. However, the effectiveness of influenza vaccination in reducing hospitalization due to cardiovascular disease is not clearly known. We aim to determine the effect of influenza vaccination on hospitalization rates due to cardiovascular disease in patients with a history of coronary heart disease. Relevant literature was searched on four electronic databases: MEDLINE, EMBASE, SCOPUS, and Cochrane Library, using predetermined keywords. Critical review of the studies was done using the Center of Evidence Based Medicine (CEBM) University of Oxford assessment tool. The search yielded six articles, and critical review was done based on validity, importance, and applicability. Three studies showed that influenza vaccination in patients with coronary heart disease would reduce hospitalization rates due to cardiovascular disease within 12 months after vaccination. Three studies did not show any effect of influenza vaccination on hospitalization rates due to cardiovascular disease. The samples in the three studies that found a protective effect of the influenza vaccine were older and at higher risk of experiencing cardiovascular events. Based on our review, we conclude that influenza vaccination can be given to prevent hospitalization due to cardiovascular disease in patients with a history of coronary heart disease, especially in high-risk patients. Keywords: Coronary heart disease, hospitalization, influenza vaccination